Quantitative light-induced fluorescence-guided surgery for medication-related osteomyelitis of the jaw - Yesel Kim; Jeong-Kui Ku (Photodiagnosis and Photodynamic Therapy)
Background: Medication-related osteonecrosis of the jaw (MRONJ) is a challenging condition with increasing incidence, and the lack of clear surgical guidelines poses difficulties in its treatment. Methods: Quantitative light-induced fluorescence (QLF), which can distinguish between vital and necrotic bone tissue without the need for additional markers, was used to guide minimally invasive surgery in a 75-year-old patient with MRONJ. Results: This study demonstrated that QLF allows the real-time identification of infected and necrotic bone tissue during surgery, enabling precise and minimally invasive resection. We observed spontaneous bone recovery and remodeling in sclerotic bone areas that exhibited autofluorescence using a QLF device, suggesting its potential for preserving the bone tissue. Conclusion: This study highlights the promising application of QLF as a valuable photodiagnostic tool in MRONJ surgery, offering a noninvasive and intraoperative device for differentiating pathological bone tissue. This approach can potentially improve the precision of surgical interventions and contribute to improved patient outcomes in MRONJ management.